2016
DOI: 10.1186/s41155-016-0023-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic alcoholism in the sensitivity to luminance contrast in vertical sinusoidal gratings

Abstract: The aim of this study was to measure visual contrast sensitivity (CS) of luminance using vertical sinusoidal gratings with spatial frequencies of 0.6, 2.5, 5.0 and 20.0 cycles per degree of visual angle in chronic alcoholics in abstinence period. The participants were 20 volunteers (26-59 years of age) divided into two groups: the study group (SG) consisted of 10 volunteers with a clinical history of chronic alcoholism abstinence and the control group (CG) consisted of 10 healthy volunteers. Each group had fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Results from the perceptual task without cues did not corroborate our first hypothesis and rather supported a generalized deficit for SF, as individuals with SAUD showed less sensitivity to the orientation of the Gabor patches than HC at all the SF considered (1.5-6.0 cpd). This result matches the findings of Cruz et al (2016) who observed a global reduction in contrast sensitivity for sinusoidal gratings sampled at 0.6, 2.5, 5, and 20 cpd, thus partially overlapping with the SF range used here. It is also consistent with Roquelaure et al (1995)'s report of reduced contrast sensitivity between 0.1 and 9.0 cpd, though we did not identify more intense deficits for the most extreme SF.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results from the perceptual task without cues did not corroborate our first hypothesis and rather supported a generalized deficit for SF, as individuals with SAUD showed less sensitivity to the orientation of the Gabor patches than HC at all the SF considered (1.5-6.0 cpd). This result matches the findings of Cruz et al (2016) who observed a global reduction in contrast sensitivity for sinusoidal gratings sampled at 0.6, 2.5, 5, and 20 cpd, thus partially overlapping with the SF range used here. It is also consistent with Roquelaure et al (1995)'s report of reduced contrast sensitivity between 0.1 and 9.0 cpd, though we did not identify more intense deficits for the most extreme SF.…”
Section: Discussionsupporting
confidence: 92%
“…Current results regarding SF processing in SAUD are mixed. Measuring the contrast sensitivity function, i.e., the inverse U-shaped function that describes how contrast sensitivity varies with SF (Campbell and Robson, 1968), some found impaired contrast sensitivity at all SF (Roquelaure et al 1995;Cruz et al 2016), whereas other did not spot any difference at any SF compared to healthy controls (de Oliveira Castro et al 2009). According to Roquelaure et al (1995), individuals with SAUD show stronger reductions in contrast sensitivity for LSF and HSF than intermediate SF, with a switch in optimal sensitivity toward lower SF ranges compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings resemble those of Zhuang et al (2012) who observed a selective reduction of MC contrast sensitivity and PC contrast gain under acute alcohol consumption. They are also consistent with reports of impaired contrast sensitivity for both low and high spatial frequencies in SAUD (da Cruz et al, 2016; Oliveira Castro et al, 2009; Roquelaure et al, 1995).…”
Section: Discussionsupporting
confidence: 90%
“…Subsequent studies confirmed the presence of visual impairments by measuring visual evoked potentials, chromatic and achromatic vision, motion and speed processing, or peripheral visual field perception (Creupelandt and Maurage, 2021). They also showed that visual processing deficits may persist with long‐term abstinence, inducing durable perceptual changes (da Cruz et al, 2016; Fein et al, 1990, 2006; Yohman et al, 1985).…”
mentioning
confidence: 99%
“…Together, behavioral studies thus identified multiple visuoperceptive deficits in SAUD, potentially implicating the whole retino‐geniculo‐cortical pathway. They also revealed that some visuoperceptive changes could last for months or even years after drinking cessation (da Cruz et al, 2016; Fein et al, 1990, 2006; Yohman et al, 1985), further justifying the need to consider their long‐term consequences. However, cerebral correlates have generally been overlooked, so that the underlying neural changes remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%